Future anxiety and its relationship to self-efficacy among high school female students in Hail - Al-Rashidi, Fydaa Ghazi (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify the future anxiety and its relationship to the self-efficacy of secondary school students in Hail city. The statistical package for the social and educational sciences (SPSS) was also used to analyze the data and treat it statistically.The following results were achieved:There is a negative correlation between future anxiety and self-efficacy where the increase in future anxiety was accompanied by a decrease in self-efficacy.An average level of future anxiety among secondary school students in Hail was revealed, and this is a positive indicator, and despite the negative effects of future anxiety on the individual, it can have positive effects and make him do his best to reduce the consequences of the threat and achieve future goals despite challenges and obstacles.The study was concluded with several recommendations, including:The necessity of paying attention to educational and psychological counseling by opening an office for psychological and educational counseling that deals with students' problems, and how to find appropriate solutions for them to achieve psychological adjustment.Providing some scientific, sports, and recreational events, programs and activities to help students relieve future anxiety.
Keywords: Future anxiety; Self-efficacy; secondary school students